SpheroMold: modernizing the hanging drop method for spheroid culture - Guimaraes, Ana Paula Pereira; Calori, Italo Rodrigo; Bi, Hong; Tedesco, Antonio Claudio (Frontiers in Drug Delivery, 2024)
The hanging drop method proves cost-effective for 3D spheroid culture. However, the laborintensive process of obtaining numerous spheroids is compounded by the risk of droplet coalescence, particularly evident during medium renewal in plates with high-density hanging droplets. In this study, we created a 3D printing-based support, termed SpheroMold, to streamline Petri dish manipulation in the hanging drop method and increase spheroid yield per unit area. To this aim, a circular digital negative mold was designed, as a proof-of-concept, consisting of 37 pegs within a 13.52 cm 2 area, and then manufactured using stereolithography.The SpheroMold was prepared by curing Sylgard 184 in the negative mold cavities and attaching it to the lid of a Petri dish. Our SpheroMold successfully inhibited droplet coalescence, particularly during handling, facilitating the formation of numerous round and viable spheroids. Unlike conventional techniques, the SpheroMold accommodated a greater volume of culture medium per drop compared to a standard Petri dish, potentially minimizing the necessity for frequent medium exchange to sustain cellular health. Our SpherodMold improves spheroid production and makes manipulation easier, leading to higher yield and viability, while decreasing labor intensity. Special attention should be paid during the extraction of the SpheroMold from the mold to preserve its structural integrity, while employing sterilization techniques such as 70% alcohol and UV radiation before use.